Le programme Feederwatch et la politique des grands nombres - Florian Charvolin (Développement Durable et Territoires)
Feederwatch program is a project dedicated to counting birds at feeders in the backyard of participants from November to April, since 1988. This program uses statistical means to calculate trends in the evolution of bird populations and areas of distribution, in order to cope, each year, with the huge cover of the program (North American continent) and consequently the huge number of lay people involved (16 000 in 2003). This case documents a successful program in « public understanding of science » oriented toward real science. This paper describes and discuss the various mechanisms aligning scientists and lay people, at each stage of the process of data collecting and processing, in what the Cornell Laboratory of Ornithology calls an example of « citizen science ».